Seasonal Assessment of Musi River Water Quality in Palembang Using STORET and PI - Faizaturrohmah, Nur; Sukmawardana, M. Iqbal; Noor Azizah, Rifka; Isoralla, Isoralla; Awfa, Dion; Rohman, Arif; Ulin Nuha, Muhammad; Try Atmojo, Aulia; Adli Naufal Purnomo, Daffa (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2026)
This study aims to determine the water quality status of the Musi River in Palembang City in the dry season (July) and the rainy season (October) using the STORET and Pollution Index (PI) methods, as a scientific basis for evaluating seasonal pollution dynamics and supporting sustainable river management. Water samples were collected from four representative sampling sites along the Musi River in Palembang City, representing the upstream reach, industrial zone, urban reach, and downstream section. Primary data were obtained from field measurements of physical and chemical parameters, while secondary data were obtained from water quality standards and related literature. Water quality determination using the STORET method was based on deviations from regulatory standards, while the PI method estimated the average pollution load. The results show that several parameters exceed the allowed limits, with the STORET method generally classifying the river as moderately polluted, whereas the PI method classifies it as lightly polluted. This study evaluated the water quality of the Musi River in Palembang City using the STORET method and the Pollution Index at four sampling locations in the dry and rainy seasons. The STORET analysis showed that four points fell into the moderately polluted category (score: -12 to -20), while the PI method showed lightly polluted throughout the area (Pij score: 2.29 to 3.07). The results underscore the urgent need for integrated pollution management to ensure regulatory compliance and protect ecosystems.